(untitled) (Scientific journal of the Fergana State University, 2025)
The article presents information about the emergence, formation and development of functional linguistics in world linguistics, as well as areas of research that should be carried out in Uzbek linguistics in functional linguistics. In recent years, the study of language not only as a means of communication, but also as a means of influence has become popular in world linguistics. Now on the agenda is the study of not only the participation of linguistic units in the communication process, but also their specialization - functionalization for a specific task. The study of their functionality is carried out comprehensively and in various aspects. The study of such means on the basis of a functional approach makes it possible to determine the process of speech formation, visual means of expressing thoughts, and the functions of lexical and phraseological units. and syntactic and stylistic features of speech units. In this sense, one can evaluate the functional capabilities of tactical units. Today, research carried out in world linguistics, including within the framework of functional syntax, is of particular practical importance in the development of this area. General issues of the functional syntax of the Uzbek language are also covered.